2009
DOI: 10.1074/mcp.m900259-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Protein-bound Tyrosine Nitration Characterized by Diagonal Chromatography

Abstract: A new proteomics technique for analyzing 3-nitrotyrosine-containing peptides is presented here. This technique is based on the combined fractional diagonal chromatography peptide isolation procedures by which specific classes of peptides are isolated following a series of identical reverse-phase HPLC separation steps. Here dithionite is used to reduce 3-nitrotyrosine to 3-aminotyrosine peptides, which thereby become more hydrophilic. Our combined fractional diagonal chromatography technique was first applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 48 publications
2
104
0
2
Order By: Relevance
“…In this study, the nitropeptides were reduced to aminopeptides followed by acetylation in order to improve fragmentation and identification. Using the COFRADIC approach, Ghesquiére et al [34] observed only one out of four peptides coinciding with our results. This most likely reflects irreproducibility of the in vitro nitration procedure rather than of the methods for isolation and identification of the nitrated peptides.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, the nitropeptides were reduced to aminopeptides followed by acetylation in order to improve fragmentation and identification. Using the COFRADIC approach, Ghesquiére et al [34] observed only one out of four peptides coinciding with our results. This most likely reflects irreproducibility of the in vitro nitration procedure rather than of the methods for isolation and identification of the nitrated peptides.…”
Section: Resultssupporting
confidence: 80%
“…showed that the COFRADIC approach could also be used to identify nitrotyrosine containing peptides in both simple and complex samples [34].…”
Section: Introductionmentioning
confidence: 99%
“…Excess radicals are scavenged by serum proteins, leading to protein modifications such as tyrosine nitration (28). Using our COFRADIC approach we next investigated whether this oxidative burst led to oxidation of methionine in serum proteins of mice infected with Salmonella.…”
Section: A Cofradic Methods For Isolating Peptides Containingmentioning
confidence: 99%
“…Following the COFRADIC sorting procedure we analyzed the obtained fractions onto an Ultimate 3000 nano-HPLC system in-line connected to a LTQ Orbitrap XL mass. Mass spectrometric analysis was performed as described (28).…”
Section: Reduction Of a Methionine Sulfoxide Peptide Using Msra Andmentioning
confidence: 99%
“…In a typical experiment, a sample is fractionated by HPLC, fractions are collected, dried, treated to modify a residue or PTM and again subjected to HPLC analysis. This technique has been used to study modifications including phosphorylation, nitration and N-glycosylation [27][28][29][30]. The latest development in this field is an automated enzyme-based approach involving capillary electrophoresis, in which the distal end of the first capillary incorporates an enzyme-based microreactor [31].…”
Section: Diagonal Separationmentioning
confidence: 99%